2021
DOI: 10.21608/jpp.2021.105615.1073
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability and Gene Action Using 10 X 10 Diallel Crosses of Ten Maize Inbred Lines (Zea mays L.)

Abstract: Ten yellow maize inbred lines were derived from different sources were evaluated in this study to estimate combining ability, type of gene action and superiority % of the F1 , s over commercial check hybrids. In 2019 grown season, all possible combinations between these lines were done in a half diallel (Griffing's 1956, method 4, model 1) to give 45 crosses at Sids Agricultural Research Station. In 2020 season, 45 crosses along two commercial hybrids; SC. 168 and SC. 3444 were evaluated in replicated trails c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
(14 reference statements)
3
4
0
Order By: Relevance
“…The correlation coefficient between LWR% showed a positive and highly significant association with GYP -1 (0.414*) and GY (0.425*). These results align with the findings of Abd El-Azeem et al (2021) and Aly et al, (2022).…”
Section: Specific Combining Abilitysupporting
confidence: 91%
“…The correlation coefficient between LWR% showed a positive and highly significant association with GYP -1 (0.414*) and GY (0.425*). These results align with the findings of Abd El-Azeem et al (2021) and Aly et al, (2022).…”
Section: Specific Combining Abilitysupporting
confidence: 91%
“…Results showed that there were highly significant differences among locations for all studied traits except for GY and DTS traits, indicating that the three locations differed in the environmental conditions. These results are similar to those obtained by Haddadi et al, (2012), Aly (2013), Abd EL-Azeem et al, (2021, Apraku et al, (2021) and Aly et al, (2022). Mean squares for crosses (C) and their interaction with locations (C × Loc) were significant and highly significant for all studied traits except for C × Loc of EHT.…”
Section: Analysis Of Variancessupporting
confidence: 89%
“…Mean squares due to GCA × Loc and SCA × Loc interactions were significant for all studied traits except for GCA × Loc and SCA × Loc of EHT and for GCA × Loc of Epos%, indicating that additive and non-additive gene effects were affected by environmental conditions in most traits. GCA × Loc was larger than SCA × Loc for all studied traits except Epos% trait, indicating that additive gene effects are more influenced by environmental than non-additive components; Abd EL-Azeem et al, (2021) for DTS and GY, Aboyousef et al, (2022) and Aly et al, (2022) for DTS, PHT, EHT and GY traits. 1.25 0.50 *, ** significant at 0.05 and 0.01 levels of probability, respectively.…”
Section: General (Gca) and Specific (Sca) Combining Ability Variancesmentioning
confidence: 82%
“…The parental lines L 1 , L 4 , L 6 , L 7 , L 8 and L 11 had desirable values toward earliness. With respect to PHT and EHT, the inbred lines L 6 , L 7 , L 8 L 10 and L 11 were the best general combiners toward shorter plant and lower ear placement, implying the tendency of this line to reduce plant height, which is very important for development of genotypes resistant to loading [1] and [4]. The best general combiners for GY ard fed −1 were L 1 and L 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Genetics Department, Faculty of Agriculture, Mansoura University, Elgomhouria St., Mansoura 35516, Egypt. 2 Maize Research Program, ARC, FCRI, Cairo, Egypt.…”
Section: Abbreviationsmentioning
confidence: 99%